Evaluation of the energy sector of Latin America and the Caribbean (2000)
Presents an overview of the current situation of the energy sector in Latin America and the Caribbean. Shows that transformation and modernization processes have consolidated the sector's importance for the region's economic and social development.
Keywords: ENERGY